Performance analysis of REST API technologies using Spring and Express.js examples - Maciej Wicha; Beata Pańczyk (Journal of Computer Sciences Institute)
The purpose of this article is a comparative analysis of two technologies for building applications in REST architecture. A Java-based development framework - Spring, and a framework designed for JavaScript language and Node environment - Express.js were analyzed. The test application was designed and implemented in both studied technologies. Using the Apache JMeter tool, HTTP request processing times were measured by operating on simple text data. The experiment was based on 5 scenarios repeated for a different number of users in the range of 10 to 100, with a constant number of executed requests to the server. The analysis conducted showed that the application implemented in Express.js handles HTTP requests up to 249% more efficiently than its counterpart in Spring.